2002
DOI: 10.1080/10586458.2002.10504485
|View full text |Cite
|
Sign up to set email alerts
|

Kashaev's Conjecture and the Chern-Simons Invariants of Knots and Links

Abstract: R.M. Kashaev conjectured that the asymptotic behavior of his link invariant, which equals the colored Jones polynomial evaluated at a root of unity, determines the hyperbolic volume of any hyperbolic link complement. We observe numerically that for knots 6 3 , 8 9 and 8 20 and for the Whitehead link, the colored Jones polynomials are related to the hyperbolic volumes and the Chern-Simons invariants and propose a complexification of Kashaev's conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 8 publications
1
83
0
Order By: Relevance
“…Then, the moduli 17 Notice, that our normalization of the Chern-Simons invariant agrees with [52,55], but differs from the normalization used in [36] by a factor of 2π 2 .…”
Section: The A-polynomial and The Generalized Volume Conjecturementioning
confidence: 99%
See 1 more Smart Citation
“…Then, the moduli 17 Notice, that our normalization of the Chern-Simons invariant agrees with [52,55], but differs from the normalization used in [36] by a factor of 2π 2 .…”
Section: The A-polynomial and The Generalized Volume Conjecturementioning
confidence: 99%
“…The volume conjecture was extended further in [36], where it was shown that for a large class of knots one can remove the absolute value in (5.3), so that the following limit…”
Section: A Brief Review Of the Volume Conjecturementioning
confidence: 99%
“…Although it looks trivial, due to the ambiguity of the optimistic limit, only few results are known. It was numerically confirmed for few examples in [12], actually proved only for the volume part of two bridge links in [13] and for the Chern-Simons part of twist knots in [2]. In a nutshell, the purpose of this paper is to propose a general method to define the optimistic limit of the colored Jones polynomial of a hyperbolic knot K and to prove the following relation:…”
Section: Preliminariesmentioning
confidence: 99%
“…The VC in the above form has been formally checked for the Figure Eight knot (Murakami and Murakami [14]), the Borromean link, for torus knots (Kashaev and Tirkkonnen [11], Murakami and Murakami [15]), their Whitehead doubles (Zheng [26]) and for the family of "Whitehead chains" (Van der Veen [25]). Moreover, there is experimental evidence of its validity for the knots 6 3 , 8 9 and 8 20 (Murakami et al [16]). …”
Section: Introductionmentioning
confidence: 99%